Vitamin D and the Serotonergic Pathway in Depression: Genomic Mechanisms, Clinical Evidence, and Implications for Sport and Physical Activity — A Narrative Review - Czechowska, Małgorzata; Kasznicki, Michał; Skrzypek, Emilia; Łącki, Jakub; Rogozińska, Alicja; Beśka, Wiktor; Jackowiak, Karol; Kalisiak, Michał; Micek, Natalia; Kamela, Mikołaj (Quality in Sport, 2026)
Background and Purpose: Vitamin D, acting through the vitamin D receptor (VDR), may directly regulate brain serotonin synthesis, linking vitamin D deficiency to depression. This review examines the serotonergic hypothesis of vitamin D action, evaluates supporting evidence, and considers implications for athletes. Materials and Methods: PubMed, Scopus, Google Scholar, and the Cochrane Library were searched for articles published between 2010 and 2026 using terms related to vitamin D, serotonin, TPH2, VDR, depression, and physical activity. Results: Calcitriol upregulates tryptophan hydroxylase 2 (TPH2), represses the serotonin transporter (SLC6A4) and monoamine oxidase A, together constituting a three-node serotonergic regulatory circuit. Meta-analyses of RCTs confirm vitamin D reduces depressive symptoms (SMD = −0.36 to −0.57), with dose-dependent effects peaking near 8,000 IU/day. Effects are strongest in deficient individuals with existing depression. VDR polymorphisms, particularly FokI, modulate the neuropsychiatric impact of deficiency. Athletes exhibit high rates of insufficiency and may benefit given overlapping exercise-vitamin D effects on serotonin. Conclusions: The serotonergic hypothesis offers a defined molecular account connecting vitamin D and depression. Future research should prioritize CSF serotonin metabolite measurements, genotype-stratified trials, and sport-specific cohort studies.